COMPARISON OF JOB SATISFACTION AND STRESS AMONG MALE AND FEMALE DOCTORS IN TEACHING HOSPITALS OF KARACHI - Khuwaja, Ali Khan; Qureshi, Riaz; Andrades, Marie; Fatmi, Zafar; Khuwaja, Nadya Khan (Journal of Ayub Medical College Abbottabad, 2004)
Background: Job dissatisfaction and stress among doctors affect the quality of health care. We assessed the levels of satisfaction for workplace characteristics and job stress among doctors of three teaching hospitals in Karachi. Methods: A postal-survey was conducted between May to June 2002. Satisfaction for workplace characteristics and stress were inquired and graded by Likert scale (1=very low to 5= very high). Questions were also asked about its affect on their lives. In order to calculate the differences in means of job satisfaction and stress score by sex of doctors, chi-square and t-test with 95% confidence interval (CI) were used. Out of 270 doctors approached conveniently, 189 (70%) responded and 182 questionnaires were found complete for analysis. Results: Majority (68%) of the doctors was not satisfied with their jobs. Overall, the mean scores for satisfaction were low for workplace characteristics. Lowest scores were found for pay and benefits 2.12 (SE 0.8), safety and security 2.15 (SE 0.8) and workload 2.69 (SE 0.9). Female doctors had significantly lower satisfaction about workload (mean job satisfaction score difference = 0.60; 95%CI, 0.24-0.97), relation with colleagues (mean job satisfaction score difference = 0.49; 95%CI, 0.11-0.87) and autonomy (mean job satisfaction score difference = 0.45; 95%CI, 0.07-0.82) as compared to their male counterparts. Overall, 48% of doctors graded job stress from high to very high levels. Conclusion:Majority of doctors working at these teaching hospitals of Karachi had poor satisfaction level for workplace characteristics and higher levels of job stress. This suggests that immediate steps should be taken for their control and management. This study invites further research to explore, implement and evaluate intervention strategies for prevention of stress and improvement in job satisfaction. Keywords: job satisfaction; stress; doctors;